Dose Optimization of Antihyperuricemia Effects of Matoa Leaf (Pometia pinnata J.R.Forst & G.Forst) in Rats - Afiah, Nurul; Santi, Irma; Putra, Bayu (Pharmaceutical Reports, 2023)
Hyperuricemia is a condition of increased uric acid levels in the blood above normal limits that can cause pain or soreness, which if not treated immediately will cause chronic gout, the formation of tofus, and severe kidney function disorders. One plant that is thought to have anti-hyperuricemia effects is matoa leaves (Pometia pinnata J.R.Forst ; G.Forst) because they contain secondary metabolite compounds, namely flavonoids. This study is an experimental study using 25 male white rats divided into 5 treatment groups, namely group I (Na-CMC, negative control), group II (Allopurinol, positive control 100 mg), group III, IV, and V were given matoa leaf ethanol extract (EEDM) with successive doses of 200 mg/kg body weight (BW), 400 mg/kg BW, and 800 mg/kg BW for 4 days. Test animals were induced with fresh chicken liver juice orally for 7 consecutive days and potassium oxonate 250 mg/kg BW intraperitoneally on day 8. On the 9th to 12th day, EEDM therapy was carried out. Measurement of uric acid levels was carried out on days 0 (before treatment), 7, 8, and 12. The data were then processed statistically using Kruskal-Wallis and the Mann-Whitney follow-up test. From the results of the study, it can be concluded that ethanol extract of matoa leaves has an effect as anti-hyperuricemia with the most effective dose being 200 mg/kg BW.